2016
DOI: 10.1177/1362361316660065
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the social communication questionnaire: Screening for autism spectrum disorder

Abstract: The current meta-analysis examines the previous research on the utility of the Social Communication Questionnaire as a screening instrument for autism spectrum disorder. Previously published reports have highlighted the inconsistencies between Social Communication Questionnaire-screening results and formal autism spectrum disorder diagnoses. The variations in accuracy resulted in some researchers questioning the validity of the Social Communication Questionnaire. This study systematically examined the accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 36 publications
3
48
1
3
Order By: Relevance
“…The AUC is considered a useful metric when considering screening measures (and diagnostic tests more broadly) as it provides a summary measure of test accuracy, taking into account both test sensitivity and specificity. Whilst other studies since this time have raised some questions about the accuracy of the SCQ as a screening tool (Corsello et al, 2007;Snow et al, 2008), a recent metaanalysis has suggested that overall the SCQ is an acceptable screening instrument for ASD but that its accuracy varies greatly depending on factors such as age at assessment, the version used and sampling strategy (Chesnut, Wei, Barnard-Brak, & Richman, 2016).…”
mentioning
confidence: 99%
“…The AUC is considered a useful metric when considering screening measures (and diagnostic tests more broadly) as it provides a summary measure of test accuracy, taking into account both test sensitivity and specificity. Whilst other studies since this time have raised some questions about the accuracy of the SCQ as a screening tool (Corsello et al, 2007;Snow et al, 2008), a recent metaanalysis has suggested that overall the SCQ is an acceptable screening instrument for ASD but that its accuracy varies greatly depending on factors such as age at assessment, the version used and sampling strategy (Chesnut, Wei, Barnard-Brak, & Richman, 2016).…”
mentioning
confidence: 99%
“…Therefore, appropriate standardized instruments are important and may support researchers and clinicians in the diagnostic decision [Hare, Mellor, & Azmi, ; La Malfa et al, ]. Although the SCQ has been validated across a wide range of ages and levels of intellectual functioning [Chesnut et al, ; National Institute of Health and Care Excellence, ; Sappok et al, ], there are few studies examining this instrument in adults with ID, a population that is particularly at risk for ASD. Improved recognition of ASD in adults with ID may not only increase quality of life and mental health of the affected individuals and their families by providing a better chance for more appropriate treatment and care, but also may lead to improved outcomes and as a result lower costs to the economy [National Audit Office, ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it should be taken into account, that the SCQ current was used in this analysis and in a current meta-analysis, Chesnut et al [1016] has shown that the current form tends to have a lower diagnostic accuracy compared to the SCQ lifetime. However, this is not the case in adults with ID as shown by Sappok, Brooks, Heinrich, McCarthy, and Underwood [2016], especially in those with more severe ID.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The social communication questionnaire [SCQ; Rutter, Bailey, & Lord, 2003] is a 40-item parent-report questionnaire designed to index the severity of impairments in social, communication, and repetitive behavior domains. It was originally suggested [Berument, Rutter, Lord, Pickles, & Bailey, 1999] that a cutoff score of 15 represents an optimal balance between sensitivity (0.85) and specificity (0.75) when screening for ASD, however, a recent metaanalysis by Chesnut, Wei, Barnard-Brak, and Richman [2017] suggests a cutoff score of 11 as more optimal (area under the curve = 0.885). Both the cutoff of 11 and 15 were used in this article.…”
Section: Procedures and Measuresmentioning
confidence: 99%